2017
DOI: 10.1186/s12864-017-4354-6
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the genetic regulation of peripheral blood transcriptome in pigs through expression genome-wide association study and allele-specific expression analysis

Abstract: BackgroundEfforts to improve sustainability in livestock production systems have focused on two objectives: investigating the genetic control of immune function as it pertains to robustness and disease resistance, and finding predictive markers for use in breeding programs. In this context, the peripheral blood transcriptome represents an important source of biological information about an individual’s health and immunological status, and has been proposed for use as an intermediate phenotype to measure immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
4
26
0
Order By: Relevance
“…In cattle, such data sets have been generated for mammary gland, liver, blood and adrenal gland and have been used to identify causative genes underlying GWAS-identified QTL [41][42][43][44][45] . In pigs, eQTL studies have been conducted in skeletal muscle, lung, adipose tissue and liver [46][47][48][49][50][51][52][53][54][55][56][57] . In poultry, genome-wide eQTL analyses have been reported for liver, bone, adrenal gland and hypothalamus [58][59][60][61] .…”
Section: Epigenome Maps and Eqtl Data Sets Enable Functional Follow-umentioning
confidence: 99%
“…In cattle, such data sets have been generated for mammary gland, liver, blood and adrenal gland and have been used to identify causative genes underlying GWAS-identified QTL [41][42][43][44][45] . In pigs, eQTL studies have been conducted in skeletal muscle, lung, adipose tissue and liver [46][47][48][49][50][51][52][53][54][55][56][57] . In poultry, genome-wide eQTL analyses have been reported for liver, bone, adrenal gland and hypothalamus [58][59][60][61] .…”
Section: Epigenome Maps and Eqtl Data Sets Enable Functional Follow-umentioning
confidence: 99%
“…In total, we identified 251 ASE genes across adipose, heart, liver and skeletal muscle. To further explore the characteristics of these ASE genes, we made a comparison with ASE genes reported in previous studies for pigs (Esteve-Codina et al, 2011;Maroilley et al, 2017;Oczkowicz et al, 2018). We found none of the ASE genes was shared across the four datasets, suggesting that ASE gene may be tissuespecific or breed-specific ( Supplementary Figure S8).…”
Section: Discussionmentioning
confidence: 94%
“…Though previous studies have focused on ASE genes to investigate the breed-of-origin effects from purebreds on crossbred individuals for bacterial resistance (Wu et al, 2015), peripheral blood (Maroilley et al, 2017), brain development (Oczkowicz et al, 2018), prenatal skeletal muscle development (Yang et al, 2018), adipogenesis and lipid metabolism (Stachowiak et al, 2018), such studies are absent for DLY three-way crossbred pigs. Here, we first estimated the distribution of heterozygous SNPs in three kinds of three-way crossbred pigs via whole genome sequencing data originated from three purebreds (including 11 Duroc, 9 Landrace and 10 Yorkshire pigs).…”
Section: Introductionmentioning
confidence: 99%
“…The great variations in different phenotypic traits of two selected sheep breeds provide an opportunity for studying molecular mechanisms underlying gene expression related to phenotypic difference between thin-and fat-tailed sheep breeds. In this study, the candidate causative genes were detected by ASE analysis, which avoid the effect of trans-acting and has become research focus in recent years [24][25][26][27][28]. We divided all sheep individuals into 15 family trios.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, high-throughput sequencing technologies allowed us to identify ASE genes at a transcriptome-wide level. Several studies in different species such as mouse [24], pig [25], cow [26], goat [27], sheep [28], mule [29] and dzo [29] have shown that the different expression levels of alleles due to ASE may lead to variation in phenotypes.…”
Section: Introductionmentioning
confidence: 99%